Evaluate the Efficacy and Safety of Anti‐Epileptic Medications for Partial Seizures of Epilepsy: A Network Meta‐Analysis. Issue 9 (27th April 2017) - Zhao, Teng; Feng, Xuemin; Liu, Jingyao; Gao, Jiguo; Zhou, Chunkui
ABSTRACT: Epilepsy is a brain and neurological disorder with high prevalence. It was reported that more than 70% of epileptic seizures were controlled by anti‐epileptic medications, whereas the lack of evidence with respect to head‐to‐head comparisons motivated researchers to seek alternative approaches that are able to provide deep insights into the profile of anti‐epileptic medications. In this study, we performed a network meta‐analysis (NMA) to evaluate the efficacy and safety of anti‐epileptic medications for partial seizures of epilepsy. Publications were retrieved from PubMed, Embase, and Cochrane Library. Then, studies were screened and selected based on the inclusion criteria. Data were extracted and a NMA was performed to combine both direct and indirect evidence. Surface under the cumulative ranking curve (SUCRA) was obtained for ranking purposes. Consistency between direct and indirect evidence was assessed by using the node‐splitting method. Seventeen anti‐epileptic medications from 90 publications were enrolled. Fifty percent responder and state of seizure freedom were studied as outcomes for efficacy; treatment emergent adverse effect (TEAE), including dizziness, somnolence, headache, fatigue, and nausea were evaluated as safety outcomes. Topiramate, levetiracetam, pregabalin, and oxcarbazepine were recommended for their relatively high efficacy and low‐risk of adverse events for partial seizures. Rufinamide was the least preferable medication due to its low efficacy and high‐risk of adverse effects. J. Cell. Biochem. 118: 2850–2864, 2017. © 2017 Wiley Periodicals, Inc. Abstract : We performed a network meta‐analysis (NMA) to evaluate the efficacy and safety of anti‐epileptic medications for partial seizures of epilepsy. fifty percent responder and state of seizure freedom were studied as outcomes for efficacy; treatment emergent adverse effect (TEAE), including dizziness, somnolence, headache, fatigue, and nausea were evaluated as safety outcomes. Topiramate, levetiracetam, pregabalin, and oxcarbazepine were recommended for their relatively high efficacy and low‐risk of adverse events for partial seizures.